Randomized study of peginterferon-alpha2a plus ribavirin vs peginterferon-alpha2b plus ribavirin in chronic hepatitis C - Rumi, Maria Grazia; Aghemo, Alessio; Prati, Gian Maria; D'Ambrosio, Roberta; Donato, Maria Francesca; Soffredini, Roberta; Del Ninno, Ersilio; Russo, Antonio; Colombo, Massimo (Gastroenterology (New York, N.Y. 1943), 2010)
Ribavirin (RBV) combined with either pegylated interferon (PegIFN) alpha2a or PegIFNalpha2b is the standard of care for chronic hepatitis C virus (HCV) infection. Due to the lack of head-to-head studies, the 2 PegIFNs have not been directly compared. The endpoints of our study were safety and antiviral efficacy of the 2 regimens. Treatment-naïve patients with chronic hepatitis C were randomly (1:1) assigned after stratification for HCV genotype to receive either 1.5 mcg/Kg/week PegIFNalpha2b plus RBV 800-1200 mg/day or 180 mcg/week PegIFNalpha2a plus RBV 800-1200 mg/day for 24 or 48 weeks according to HCV genotype. The study was powered to detect a difference of at least 10% in safety and efficacy of the 2 regimens. The 212 patients on PegIFNalpha2a and the 219 patients on PegIFNalpha2b had similar baseline characteristics, including cirrhosis (20% vs 18%, respectively). By intention to treat, the 2 groups showed similar rates of treatment-related serious adverse events (1% vs 1%, respectively) and drop out rates for adverse effects (7% vs 6%, respectively). Overall, sustained virologic response (SVR) rate was higher in PegIFNalpha2a than in PegIFNalpha2b patients (66% vs 54%, respectively, P = .02), being 48% vs 32% in the 222 HCV-1 and -4 patients (P = .04), and 96% vs 82%, respectively, in the 143 HCV-2 patients (P = .01). PegIFNalpha2a independently predicted SVR in the logistic regression analysis (odds ratio, 1.88; 95% confidence interval: 1.20-2.96). Although the 2 regimens showed a similar safety profile, the PegIFNalpha2a-based treatment yielded significantly more SVR than PegIFNalpha2b.